Observation of photon-induced $W^+W^-$ production in $pp$ collisions at $\sqrt{s}=13$ TeV using the ATLAS detector - Fiolhais, M. C. N. (2020)
41 pages in total, author list starting page 25, 6 figures, 2 tables, published in Phys. Lett. B.. All figures including auxiliary figures are available at http://atlas.web.cern.ch/Atlas/GROUPS/PHYSICS/PAPERS/STDM-2017-21